IS THERE A SIGNIFICANT RELATIONSHIP BETWEEN THE USE OF SIMPLE EXPERIMENTAL METHODS AND IMPROVED SCIENCE LITERACY?: A CASE STUDY OF PGSD STUDENTS - Umardianti, Urmila; Bintoro Aji, Ifan Anom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of which is clear presented For study This that is know correlations that exist in the implementation of the trial simple along with scientific literacy among PGSD students . The low score national science literacy as well as perception that science is difficult subject for student prospective teachers become background behind main he did study this . Research This use approach quantitative with design correlational against 53 samples first semester students selected 2025/2026 academic year through purposive sampling technique. Data collection was carried out in a way implementation questionnaire found from trial results simple as well as test scientific literacy that has been through validity and reliability tests . Researchers using descriptive statistics and inferential statistics as technique data analysis through testing correlation Pearson product moment. Based on the design that has been determined , then found results existence contribution active students who improved on the experiment simple which is in numbers (50%), while the average score student scientific literacy reached 80.32. The results of the hypothesis test showed a significance value of 0.001 < 0.05 with a correlation coefficient of 0.990. This proves a very strong positive relationship, which means that the higher the intensity of the use of simple experimental methods, the higher the scientific literacy of PGSD students. This finding confirms that simple experiments can be a strategic solution for teacher-producing institutions in improving the quality of scientific literacy of prospective educators without relying on the sophistication of laboratory facilities.